Live birth/parity number and the risk of incident hypertension among parous women during over 13 years of follow‐up - Seyyed Saeed Moazzeni; Samaneh Asgari; Fereidoun Azizi; Farzad Hadaegh (The Journal of Clinical Hypertension, 2021)
Abstract The effect of live birth/parity number on incident hypertension was investigated among Iranian parous women aged 30–70 years. The study population included 2188 normotensive women who were enrolled in 1999–2001. They were followed for incident hypertension (based on JNC 7 report) by 3‐year intervals up to April 2018. Multivariable Cox proportional hazard models, adjusted for a wide set of potential hypertension risk factors, reproductive factors, and pregnancy complications, were applied to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) of the number of parity/live birth(s) for incident hypertension. Additionally, as a sensitivity analysis, age‐scale Cox regression was also done. During a median follow‐up of 13.5 years, 935 incident hypertension have occurred. Compared to those with two live births, the participants who had 3 and ≥4 live births were at higher risk of hypertension development by the HRs of 1.25 [95% CI: 1.02–1.55] and 1.39 [1.12–1.72], respectively, in the full‐adjusted model. Moreover, each additional live birth increased the risk of hypertension by a HR of 1.06 [95%CI: 1.02–1.11]. Results of parity number were also similar. Considering age as time scale also did not change the results generally. The authors found a significant interaction between live birth/parity number and age groups; the adverse effect of higher live birth/parity numbers on hypertension development was mainly found among those aged < 50 years. To sum up, compared to the live birth/parity number of two, Iranian women with ≥3 live birth/parity had a higher risk of incident hypertension; the issue was more prominent among younger mothers.